2001
DOI: 10.1016/s0896-6273(01)00219-7
|View full text |Cite
|
Sign up to set email alerts
|

A Developmental Switch in Neurotransmitter Flux Enhances Synaptic Efficacy by Affecting AMPA Receptor Activation

Abstract: Formation of glutamatergic synapses entails development of "silent" immature contacts into mature functional synapses. To determine how this transformation occurs, we investigated the development of neurotransmission at single synapses in vitro. Maturation of presynaptic function, assayed with endocytotic markers, followed accumulation of synapsin I. During this period, synaptic transmission was primarily mediated by activation of NMDA receptors, suggesting that most synapses were functionally silent. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
149
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(160 citation statements)
references
References 67 publications
(3 reference statements)
10
149
0
1
Order By: Relevance
“…However, if those from 2 animals showed a significant difference, then a third animal was included in the count. Immunogold labeling was not counted per unit length of the synapse, because we found in our previous study that the values of gold per synapse versus gold per micrometer length of the synapse were similar for these ages ; lack of significant change of synapse length during development is noted also for hippocampal neurons in vitro by Renger et al [2001] and reviewed in general by Ziv and Garner [2004]). Thus, the gold per synapse values given here can be compared readily with those already published using the same method Sans et al, 2000); this is the most efficient method of comparing results among proteins found in the same region and during the same developmental sequence.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…However, if those from 2 animals showed a significant difference, then a third animal was included in the count. Immunogold labeling was not counted per unit length of the synapse, because we found in our previous study that the values of gold per synapse versus gold per micrometer length of the synapse were similar for these ages ; lack of significant change of synapse length during development is noted also for hippocampal neurons in vitro by Renger et al [2001] and reviewed in general by Ziv and Garner [2004]). Thus, the gold per synapse values given here can be compared readily with those already published using the same method Sans et al, 2000); this is the most efficient method of comparing results among proteins found in the same region and during the same developmental sequence.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Interestingly, the bacterial networks exhibit a topology similar to the network proposed by Kneussel and Betz (2000) for the clusters of GABA and glycine receptors. Furthermore, the receptors are not frozen in this complex environment and their distribution patterns can be modified by activity (Renger et al, 2000). Neurotransmitter receptors can move across the plasma membrane, and aggregate (Meier et al, 2001;SergĂ© et al, 2002), and even can be transferred back and forth to an intracellular pool (Barry and Ziff, 2002).…”
Section: Intracellular Targeting and Receptor Clusteringmentioning
confidence: 99%
“…It has been proposed that a similar mechanism might underlie the conversion of immature silent synapses into mature functional synaptic contacts. 56 Although Choi et al 55 favored the fusion pore explanation, they did not rule out that the slow-rising EPSCs could be generated instead by spillover from neighbor synapses rather than from a slow releasing fusion pore. Recently, Nielsen et al 57 have reported that at cerebellar mossy fiber-granule cell synapses glutamate spillover from other synapses is the main cause for slow-rising EPSCs.…”
Section: Presynaptic Ltp Independent Of Nmda Receptormentioning
confidence: 99%